2016
DOI: 10.1371/journal.pone.0163524
|View full text |Cite|
|
Sign up to set email alerts
|

Decreased Sperm Motility Retarded ICSI Fertilization Rate in Severe Oligozoospermia but Good-Quality Embryo Transfer Had Achieved the Prospective Clinical Outcomes

Abstract: IntroductionSpermatozoa motility is the critical parameter to affect the treatment outcomes during assisted reproductive technologies (ART), but its reproductive capability remains a little informed in condition of severe male factor infertility. This retrospective cohort study aimed to evaluate the effects of reduced sperm motility on the embryological and clinical outcomes in intra-cytoplasmic sperm injection (ICSI) treatment of severe oligozoospermia.Patients and Methods966 cycles (812 couples) of severe ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…We considered the hypothesis that in ICSI cycles where one spermatozoa with better quality parameters is chosen and injected in the oocyte, the intrinsic quality is still affected by the general semen quality, and it is impossible to tell the best spermatozoa based on the genetic information alone. Therefore, the potential of embryo development is also affected ( Zheng et al ., 2016 ). Based on the group classifications, we evaluated the effects of semen quality on blastocyst development in a large cohort of patients/oocytes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We considered the hypothesis that in ICSI cycles where one spermatozoa with better quality parameters is chosen and injected in the oocyte, the intrinsic quality is still affected by the general semen quality, and it is impossible to tell the best spermatozoa based on the genetic information alone. Therefore, the potential of embryo development is also affected ( Zheng et al ., 2016 ). Based on the group classifications, we evaluated the effects of semen quality on blastocyst development in a large cohort of patients/oocytes.…”
Section: Discussionmentioning
confidence: 99%
“… Zheng et al (2016) demonstrated that a reduced number of motile spermatozoa diminished fertility and embryo quality on day 3; however, if there was a good embryo for transfer, the likelihoods of implantation and pregnancy were similar. Then, it was suggested that the implantation rate was the important parameter to evaluate the ability of an individual embryo to be implanted and it was not associated with sperm quality ( Zheng et al ., 2016 ). We did not evaluate the clinical outcomes, which is a limitation of this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies either focused on the outcomes and safety of ICSI with sperms from different sources 7 8 9 10 11 12 or were solely concerned about the clinical outcomes of oligozoospermia. 13 14 However, there is a lack of conclusive data on ICSI outcomes based on the semen retrieval method and sperm concentration in males with azoospermia to mild oligozoospermia. We retrospectively collected 1201 ICSI cycles performed due to male azoospermia or oligozoospermia in males from January 2015 to December 2015.…”
Section: Introductionmentioning
confidence: 99%